2021
DOI: 10.1016/j.electacta.2021.137820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure and temperature on carbon dioxide reduction at a plasmonically active silver cathode

Abstract: Carbon dioxide reduction at a plasmonically active silver cathode was investigated by varying the pressure and temperature at multiple applied potentials under both dark and illuminated conditions to understand the mechanism of selectivity changes driven by plasmon-enhanced electrochemical conversion. Carbon dioxide partial pressures (P CO2 ) from 0.2 to 1 atm were studied during linear sweep voltammetry and chronoamperometry at -0.7, -0.9, and -1.1 V RHE . At a given applied overpotential the total current de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…As for the intricate plasmonic and thermal photoelectrochemical CO 2 RR, temperature and partial pressures of CO 2 across a range of applied potentials were comprehensively studied for CO 2 RR on a plasmonic Ag cathode. 124 This in-depth investigation showed that plasmon and thermal-enhanced electrochemical conversion could modulate an exact selectivity product. As the light enhanced CO and suppressed H 2 at −0.7 V vs. RHE, formate production was maximized at −0.9 V vs. RHE in light.…”
Section: Synergistic Properties In Plasmonic Catalysismentioning
confidence: 89%
“…As for the intricate plasmonic and thermal photoelectrochemical CO 2 RR, temperature and partial pressures of CO 2 across a range of applied potentials were comprehensively studied for CO 2 RR on a plasmonic Ag cathode. 124 This in-depth investigation showed that plasmon and thermal-enhanced electrochemical conversion could modulate an exact selectivity product. As the light enhanced CO and suppressed H 2 at −0.7 V vs. RHE, formate production was maximized at −0.9 V vs. RHE in light.…”
Section: Synergistic Properties In Plasmonic Catalysismentioning
confidence: 89%
“…[18][19][20][21] Additionally, other factors, such as temperature and pH (more critically local pH, since it can differ substantially from the bulk value, especially under high current density/low buffer capacity conditions) also influence the product selectivity during the eCO 2 RR. [22][23][24] Table 1 provides several examples of eCO 2 RR products generated in aqueous media and their reversible potentials (E°′) vs. the reversible hydrogen electrode (RHE). Significant drawbacks of eCO 2 RR in aqueous solutions are the low solubility of CO 2 resulting in low current densities, the presence of a competitive hydrogen evolution reaction (HER) which suppresses the overall eCO 2 RR efficiency, in addition to sluggish kinetics and hence a large overpotential required to produce commercially desirable products at a sufficient rate.…”
Section: Introductionmentioning
confidence: 99%
“…18–21 Additionally, other factors, such as temperature and pH (more critically local pH, since it can differ substantially from the bulk value, especially under high current density/low buffer capacity conditions) also influence the product selectivity during the eCO 2 RR. 22–24 Table 1 provides several examples of eCO 2 RR products generated in aqueous media and their reversible potentials ( E °′) vs . the reversible hydrogen electrode (RHE).…”
Section: Introductionmentioning
confidence: 99%
“…A photocurrent density of −0.34 mA cm –2 was obtained upon light irradiation producing CO with 70% of Faradaic efficiency (FE) . It was suggested that light irradiation might assist CO desorption from the catalyst surface by the electrons excited from LSPR relaxation. , …”
mentioning
confidence: 99%
“…32 catalyst surface by the electrons excited from LSPR relaxation. 33,34 We previously reported a photoassisted electrochemical (PAEC) CO 2 reduction system. 35 A three-electrode flow cell with GDE was fabricated as a cathode with a plasmonic catalyst of Au nanoparticles (Au NPs) deposited on Ag nanowires (Au NWs).…”
mentioning
confidence: 99%